Electrical Power Distribution System modeling with VHDL-AMS for the construction of a Real-Time Digital Simulator using FPGAS devices - Ibarra Hernandez, Frank Alberto [UNESP]; Canesin, Carlos Alberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This paper presents a distribution feeder simulation using VHDL-AMS, considering the standard IEEE 13 node test feeder admitted as an example. In an electronic spreadsheet all calculations are performed in order to develop the modeling in VHDL-AMS. The simulation results are compared in relation to the results from the well knowing MatLab/Simulink environment, in order to verify the feasibility of the VHDL-AMS modeling for a standard electrical distribution feeder, using the software SystemVision™. This paper aims to present the first major developments for a future Real-Time Digital Simulator applied to Electrical Power Distribution Systems. © 2012 IEEE.
Keywords: Distribution power systems; FPGA devices; Hardware description languages; Real-time digital simulation; VHDL-AMS; Distribution feeders; Electrical distribution feeders; Electrical power distribution systems; Electronic spreadsheets; IEEE 13 node test feeders; MATLAB/Simulink environment; Real time digital simulation; Real-time digital simulator; Computer hardware description languages; Computer simulation; Current limiting reactors; Electric load distribution; Electric power distribution; Feeding; Industrial applications; Digital devices